When Customer Accounts Go ‘Mati Suri’: Multiple Interpretations of Privacy and the Confusion of Indonesian Cyber Law - Syahril, Muh. Akbar Fhad; Kriviņš, Anatolijs (Amsir Law Journal, 2025)
This article examines the complex legal and practical challenges arising from the implementation of dormant account blocking policies by financial institutions in Indonesia, an increasingly urgent issue amid the acceleration of digital banking and the intensification of cybercrimes. Using a normative juridical approach supported by statutory and case analysis, the research scrutinises the intersection between the need to combat financial crimes and the imperative to protect customers' privacy rights under Indonesian cyber law. The findings reveal that while dormant account blocking is effective in mitigating illegal acts, such as money laundering and misuse of digital financial accounts, it often raises procedural and ethical issues, including a lack of notification, inconsistent legal implementation, and potential infringement on consumers' rights to privacy and access. These gaps lead to eroded public trust in digital banking due to uncertainty and the risk of arbitrary administrative action. The study recommends harmonisation of regulations and standard operating procedures among banks, enhanced dispute resolution mechanisms, and strengthened protection of customers' legal and privacy rights, particularly through improved transparency and digital literacy initiatives. The article contributes an integrative conceptual model balancing risk-based financial legislation and rights-based legal protection, offering a new legal framework better suited to Indonesia's evolving financial digital landscape